Effects of a behavior developing program for prevention of stroke among patients with hypertension at Borabue district, Mahasarakham province - Yotda, Preedee; Iemsawasdikul, Warinee; Nuysri, Mukda (Thai Journal of Nursing, 2020)
The objectives of this quasi-experimental research were to compare the differences of stroke preventive behaviors and blood pressure in an experimental group before and after experiment, and after experiment between the experimental group and a comparison group. The sample comprised the 66 hypertension patients who registered to Huanong sub-district health promoting hospital and Wangplado sub-district health promoting hospital, Borabue district, Mahasarakham province, and had stroke risk at the low and the moderate levels. They were purposively selected as inclusion criterias and equally divided into the experimental group and the comparison group. The experimental tool was the behavior developing program for prevention of stroke among patients with hypertension including three factors based on the PRECEDE-PROCEED model of Green and Kreuter. The data collecting tool was a questionnaire on general data and stroke preventive behaviors. Its content validity index and Cronbach’s alpha were equal to 0.80, (2) mercury sphygmomanometer. Data were analyzed by descriptive statistics, t-test, Wilcoxon Signed Ranks test, and Mann-Whitney U test. The results were founded as follows. (1) After experiment, overall and every aspect of stroke preventive behaviors of the experimental group were significantly higher than before experiment (p < .05), and were significantly increased more than the comparison group (p < .05). (2) After experiment, the systolic and the diastolic blood pressure of the experimental group were significantly lower than before experiment and systolic blood pressure of the experimental group significantly decreased more than the comparison group (p < .05), but the diastolic blood pressure did not significantly decrease from the comparison group (p > .05).